Comment on: "Spin-0 scalar particle interacts with scalar potential in the presence of magnetic field and quantum flux under the effects of KKT in 5 D cosmic string spacetime" - Fernández, Francisco Marcelo (2022)
We show that the meaning of the eigenvalues of a radial equation derived from a powerseries method was misunderstood. The roots stemming from the truncation of the power series through a three-term recurrence relation are not the energies of the quantummechanical model under study but isolated particular eigenvalues of different models. The supposed dependence of the intensity of the magnetic field on the quantum numbers is just an artifact of the truncation method.